Comparison of the diagnostic values of HITS and CTS2 in domestic violence screening - Mojgan Mirghafourvand; Sakineh Mohammad Alizadeh Charandabi; Mohammad Asghari Jafarabadi; Sonia Asadi (Tehran University of Medical Sciences, 2016)
Background & Aim: Violence against women is a serious social problem affecting public health. Given the relatively high prevalence of domestic violence and the need for screening, a simple tool for its correct diagnosis in a short time seems to be necessary. This study aimed to compare the diagnostic values of the HITS (Hurts, Insults, Threaten, and Screams) tool and CTS2 (Revised Conflict Tactics Scales) in domestic violence screening. Methods & Materials: This cross-sectional study was conducted on 279 married women referred to health centers in Tabriz in 2014. Data were collected using the socio-demographic questionnaire, HITS and CTS2. Kappa index was used to assess agreement between instruments. Results: Results showed that HITS tool had relatively good sensitivity (75.7%) and high specificity (93.5%). Positive predictive value and negative predictive value were 96.8% and 59.5% respectively. There was a moderate agreement between instruments (Kappa=0.6). Conclusion: Given the simplicity of HITS and the possibility to complete it in a short time, this questionnaire can be recommended to identify people experiencing domestic violence at the broad level. In addition, the development of this tool is recommended in future studies.